Evaluation of Good Medicine Distribution Methods (Cdob) and Implementation by Two Pharmaceutical Wholesalers (Pbf) in Jambi City - Fahrinnisa Nabila PUTRI, Fahrinnisa; Rasmala DEWI; Rifani Bhakti Natara (RADINKA JOURNAL OF HEALTH SCIENCE, 2023)
Pharmaceutical Wholesaler (PBF) is a company that distributes medicines to hospital installations, health centers, and pharmacies so that they can be given directly to patients or the public. One of the conditions that has been determined by existing regulations is that each PBF must have a Responsible Pharmacist who is responsible for implementing the provisions for procurement, storage, and distribution of medicines and/or medicinal substances. Good Medicine Distribution Method (CDOB) is the distribution of medicines or medicinal substances that have the aim of ensuring quality when distributing or dispensing medicines and medicinal substances so that they can be properly maintained under the requirements and intended use. Implementation of Good Medicine Distribution Methods at two PBFs, namely PBF X and Y, Jambi City. This research used a non-experimental descriptive design using questionnaires and direct interviews with the pharmacist in charge (APJ) and warehouse head. The results obtained by Good Medicine Distribution Methods from the 56-question PBF X and Y questionnaire fulfill the implementation of Good Medicine Distribution Methods. The research results obtained indicate that the percentage of PBF